Genocidas ir rezistencija Nr. 23(1) - Streikus, Arūnas; Grybkauskas, Saulius; Bubnys, Arūnas; Brandišauskas, Valentinas; Kuklytė, Birutė; Burinskaitė, Kristina; Okuličiūtė, Lina (Genocidas ir rezistencija, 2008)
Pilnas leidinys